Changing Borehole Length to Improve Breakage: a Case History - Richard L. Ash; Norman S. Smith (International Society of Explosives Engineers, 1976)
Many factors affect rock fragmentation from blasting. One variable seldom considered when designing blasts, however, is the borehole length. An example is described of how the length was adjusted to give better breakage when using 4-inch diameter blastholes at a quarry. To explain the basic principles involved test results from experiments conducted by the authors where borehole lengths were altered are presented and evaluated.